The Impact of ESG on the Performance of Philippine-Listed Firms: The Role of Audit Quality and CEO Duality - Leo Delaric Manansala; Elma Lim Mallorca (AIBPM Publisher, 2025)
This study investigates the relationship between ESG performance and firm outcomes in Philippine-listed companies from 2012 to 2023, considering the moderating roles of audit quality, discretionary accruals (DACC), and CEO duality. Using data from 20 publicly listed firms and the Generalized Method of Moments (GMM), the findings reveal that higher ESG scores positively impact market-based performance metrics such as the Price-to-Book (P/B) ratio and EV/EBITDA, supporting the notion that strong ESG practices are valued by the market. Audit quality, measured by audit fees, strengthens this relationship, indicating that robust external oversight enhances confidence in ESG disclosures. On the other hand, high DACC—indicating earnings manipulation—negatively affects the ESG-performance link, suggesting that market participants may devalue ESG efforts if earnings are perceived as manipulated. CEO duality also moderates the relationship, with its effects depending on the governance context. The study highlights the complex, context-dependent nature of ESG’s impact on firm performance and underscores the importance of governance practices in realizing the financial benefits of ESG initiatives.